Prevalence, severity, and associated factors in women in East Asia with moderate-to-severe vasomotor symptoms associated with menopause. Issue 5 (28th May 2022) - Yu, Qi; Chae, Hee-Dong; Hsiao, Sheng-Mou; Xie, Jipan; Blogg, Martin; Sumarsono, Budiwan; Kim, Soyoung
Abstract: Objective: To understand prevalence, severity, impact, and treatment of vasomotor symptoms associated with menopause, using cross-sectional survey data. Methods: This online, two-part survey was conducted in East Asia among women 40-65 years recruited from established online panels (Edelman, Beijing; Hankook Research, Seoul; Rakuten Insight, Taipei) using stratified sampling. Part I collected demographics/disease characteristics, including menopausal status and vasomotor symptom severity. Women with moderate-to-severe vasomotor symptoms completed Part II, including clinical characteristics, health-related quality of life, and healthcare-seeking behavior. Primary endpoints included vasomotor symptom prevalence and severity and proportions of women eligible and willing to take hormone therapy. Results are presented for each of the three online panels separately and as a pooled total. All analyses are descriptive with no formal hypothesis testing across groups. Results: Numbers of peri- versus postmenopausal women completing Part I were Edelman, 1, 588 (55.1% vs 44.9%); Hankook Research, 1, 000 (43.6% vs 56.4%); Rakuten Insight, 773 (61.7% vs 38.3%). Vasomotor symptom prevalence was =80% in each region; overall moderate-to-severe vasomotor symptom prevalence was 55%; >50% of women were untreated. Most of those treated used non-prescription treatments. Menopausal hormone therapy use was reported by 11.6% of peri- and 7.2% of postmenopausal women. In peri- and postmenopausal women with moderate-to-severe vasomotor symptoms, 8.6% and 3.4%, respectively, were hormone therapy-willing, 19.3% and 16.8% hormone therapy-contraindicated, 25.4% and 23.0% hormone therapy-cautious, and 10.2% and 8.3% hormone therapy-averse. Women experienced significant burden on health-related quality of life and substantial impairment of work productivity and daily activities. Conclusions: Vasomotor symptoms associated with menopause affected =80% of women aged 40 to 65 years. A substantial proportion of women are unsuitable for, or choose not to take, menopausal hormone therapy, resulting in an unmet need for nonhormonal treatment options.